Strengthening Mathematics Teachers Subject Matter Knowledge for Teaching Critical Thinking through the SUPER-LS - Fitriati Fitriati; Roslinda Rosli; Arif Hidayat; Cut Khairunnisak (Universitas Syiah Kuala, 2025)
Teaching critical thinking in mathematics classroom is challenging. Mathematics teachers need a strong foundation of subject matter knowledge (SMK) to be able to design and conduct a mathematics lesson focuses on critical thinking. However, this knowledge was found low among the teachers. A community learning play important role in overcome teacher problems. One of community learning plafform that can be used to facilitate teacher to strengthen their SMK is a school-university partnership mediated by lesson study (SUPER-LS) program. Thus, this study used the SUPER-LS program to facilitate mathematics teachers to develop their subject matter knowledge (SMK) and students critical thinking. The qualitative approach was used in this study involving 10 in-service teachers (ISTs) and 59 students. Lesson study artefacts were employed to collect data and analyzed using transcrib based lesson analysis and performance assessment of critical thinking scale. The study discovered that the SUPER-LS program can facilitate collaboration among ISTs to develop and strengthen their SMK with specialize content knowledge (SCK) appear dominant. In addition, students proficiency in each indicator of critical thinking ranged from level 1 to level 4. The majority of students had a proficiency level of 2 in each indicator. However, sustain SUPER-LS program is required to improve students critical thinking performance.